Total nitrogen removal in membrane sequencing batch bioreactor treating domestic wastewater - Belli, Tiago José (2014)
This study aimed to evaluate the performance of a sequencing batch membrane bioreactor (SBMBR) in wastewater treatment for total nitrogen removal. The reactor, which was built on a pilot scale with a volume of 30 L, was operated for 154 days and fed with synthetic wastewater. The SBMBR was operated under a sequencing batch regime with a total cycle time of 4 hours, which was broken down into 5 min. at the feeding stage, 55 min. of an anoxic phase and 180 min. of aeration and filtration. The permeation flux used was 5.55 L m-2 h-1. The membrane bioreactor presented very efficient biological wastewater treatment, with COD, ammoniacal nitrogen and total nitrogen removal efficiency of 99, 98 and 96%, respectively. The high total nitrogen removal observed indicates that the SBMBR was able to promote effective nitrification and denitrification, with a concentration below 10 mg L-1 of this parameter in the permeate.